The role of livestock products for nutrition in the first 1,000 days of life - Alonso, Silvia; Domínguez-Salas, Paula; Grace, Delia (Oxford University Press, 2019)
Implications Meat, milk, and eggs are nutrient-rich products that could efficiently boost nutrient-poor diets either as part of the normal diet or if access is increased through interventions. The scientific evidence for the role of livestock products in improving nutrition is limited, especially during the first 1,000 d of life in low- and middle-income countries. Beyond producing food, the livestock sector has additional positive and negative impacts on human health, the environment, societies, and economies that must be understood and managed.